1992
DOI: 10.1063/1.350500
|View full text |Cite
|
Sign up to set email alerts
|

Influences of a high excitation frequency (70 MHz) in the glow discharge technique on the process plasma and the properties of hydrogenated amorphous silicon

Abstract: Hydrogenated amorphous silicon has been prepared at a plasma excitation frequency in the very-high-frequency band at 70 MHz with the glow discharge technique at substrate temperatures between 280 and 50 °C. The structural properties have been studied using hydrogen evolution, elastic recoil detection analysis, and infrared spectroscopy. The films were further characterized by dark and photoconductivity and by photothermal deflection spectroscopy. With respect to films prepared at the conventional frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…It has also been reported that the maximum energy Em,, of ion bombardment shifts to lower values, although the total ion flux to the growing surface increases, as the discharge frequency is increased (Heintze et al 1993b). In this study Vpp decreases from about 150 to 70V as the frequency was varied from 13.56 to 65 MHz in much the same manner as obtained by Finger et al (1992). Following the procedure adopted by Kohler, Horne and Coburn (1985), where Em,, was estimated to be about Vppp/4 (eV), Emax had a wide variation with frequency in this study.…”
Section: Discussionsupporting
confidence: 81%
“…It has also been reported that the maximum energy Em,, of ion bombardment shifts to lower values, although the total ion flux to the growing surface increases, as the discharge frequency is increased (Heintze et al 1993b). In this study Vpp decreases from about 150 to 70V as the frequency was varied from 13.56 to 65 MHz in much the same manner as obtained by Finger et al (1992). Following the procedure adopted by Kohler, Horne and Coburn (1985), where Em,, was estimated to be about Vppp/4 (eV), Emax had a wide variation with frequency in this study.…”
Section: Discussionsupporting
confidence: 81%
“…[79][80][81]. Finger et al also observed that an increased ion flux resulted in less hydrogen contributing to the stretching mode peak between 2060 and 2100 cm -1 [82]. In the ETP close to the substrate atomic hydrogen and energetic ions are nearly present [e.g.…”
Section: Measurementsmentioning
confidence: 99%
“…[4][5][6] The shift of ion energy to lower value is to be expected in VHF deposition of SiH x films. However, only few experimental measurements of ion characteristics in rf discharge have been reported.…”
Section: Introductionmentioning
confidence: 93%